Psychosocial working conditions as determinants of concerns to have made important medical errors and possible intermediate factors of this association among medical assistants - a cohort study - Viola Mambrey; Peter Angerer; Adrian Loerbroks (BMC, 2022)
Abstract Objective We sought to examine the association of psychosocial working conditions with concerns to have made important medical errors and to identify possible intermediate factors in this relationship. Methods We used data from 408 medical assistants (MAs) in Germany who participated in a 4-year prospective cohort study (follow-up period: 03-05/2021). Psychosocial working conditions were assessed at baseline by the effort-reward imbalance questionnaire and by a MA-specific questionnaire with seven subscales. MAs reported at follow-up whether they are concerned to have made an important medical error throughout the last 3 months, 12 months or since baseline (yes/no). These variables were merged into a single variable (any affirmative response vs. none) for primary analyses. Potential intermediate factors measured at baseline included work engagement (i.e., vigor and dedication, assessed by the UWES), work satisfaction (COPSOQ), depression (PHQ-2), anxiety (GAD-2) and self-rated health. We ran Poisson regression models with a log-link function to estimate relative risks (RRs) and 95% confidence intervals (CIs). Doing so, we employed the psychosocial working condition scales as continuous variables (i.e. z-scores) in the primary analyses. Potential intermediate factors were added separately to the regression models. Results Poor collaboration was the only working condition, which was significantly predictive of the concern of having made an important medical error (RR = 1.26, 95%CI = 1.00-1.57, p = 0.049). Partial intermediate factors in this association were vigor, depression and anxiety. Conclusion We found weak and mostly statistically non-significant associations. The only exception was poor collaboration whose association with concerns to have made an important medical error was partially explained by vigor and poor mental health.